2012
DOI: 10.1124/jpet.112.196113
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Neurokinin-1 Receptors Increases the Excitability of Guinea Pig Dorsal Root Ganglion Cells

Abstract: The suppression of overactive bladder symptoms in patients and overactive bladder reflexes in animal models by neurokinin (NK)-1 receptor antagonists raises the possibility that these drugs target sensory neurons. This mechanism was evaluated by examining the interactions between a specific NK-1 agonist, [Sar 9 ,Met(O 2 )(11)]-substance P (Sar-Met-SP), and a potent NK-1 antagonist, netupitant (NTP), on small size (20 -30 m) dissociated L6 and S1 dorsal root ganglion (DRG) neurons from female guinea pigs. Cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 40 publications
(75 reference statements)
1
13
0
Order By: Relevance
“…Further, TAK‐637 inhibited the spinal vesico‐vesical reflex induced by electrical stimulation of the proximal part of the pelvic nerve in spinal animals, but had no effect on carbachol or electrical field stimulation induced contraction of isolated bladder muscle strip . Netupitant has been shown to suppress acetic acid induced bladder overactivity in guinea pigs in‐vivo and inhibited the excitatory effect of [Sar(9), Met(O2)(11)]‐substance P, a specific NK‐1 agonist . Together, these results support that NK‐1 RAs inhibit the micturition reflex by acting on the spinal cord, without affecting cholinergic mechanisms and that activation of NK‐1 receptors in primary sensory neurons may play an important role in the generation of OAB.…”
Section: Discussionmentioning
confidence: 57%
“…Further, TAK‐637 inhibited the spinal vesico‐vesical reflex induced by electrical stimulation of the proximal part of the pelvic nerve in spinal animals, but had no effect on carbachol or electrical field stimulation induced contraction of isolated bladder muscle strip . Netupitant has been shown to suppress acetic acid induced bladder overactivity in guinea pigs in‐vivo and inhibited the excitatory effect of [Sar(9), Met(O2)(11)]‐substance P, a specific NK‐1 agonist . Together, these results support that NK‐1 RAs inhibit the micturition reflex by acting on the spinal cord, without affecting cholinergic mechanisms and that activation of NK‐1 receptors in primary sensory neurons may play an important role in the generation of OAB.…”
Section: Discussionmentioning
confidence: 57%
“…It remains under debate whether DRG neurons possess functional NK1r. Rodent DRG cells can express NK1r mRNA [3; 53; 102], and SP can evoke depolarizing currents in DRG cells [53; 109]. Conversely, immunohistochemical evidence for NK1r on sensory neurons and their terminals is limited (supplemental data) [14; 54; 64; 77].…”
Section: Discussionmentioning
confidence: 99%
“…TRPV1-positive sensory fibres express NK 1 and NK 2 receptors as well as produce the selective ligands substance P and neurokinin A, which are released in response to nociceptive stimulation and may produce paracrine or autocrine effects that amplify the nociceptive process [63]. In fact, NK 1 and NK 2 receptors expressed by sensory nerves cause sensitisation of TRPV1 receptors, increase neuronal excitability and induce nociception in rodents [63], [64], [65]. We observed that a combination of NK 1 and NK 2 receptor antagonists was as efficacious as the antagonists alone to reduce PNV-induced nociception, but was less efficacious than sensory nerve ablation.…”
Section: Discussionmentioning
confidence: 99%